ANALISIS PENGUKURAN KINERJA PT X DENGAN PENDEKATAN BALANCE SCORE CARD - Sibarani, Bintang B. (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
The Balanced Score Card method is used to measure company X's performance in terms of fourperspectives; financial, customer, business operational, learning and growth. Primary data are used forcustomer perspectives, operational and business, learning and growth. Whereas the financial perspectiveuses secondary data; audited financial statements. The presentation technique uses descriptive analysis, thedata collected is processed and analyzed quantitatively through answer by Likert scale. A bit for the financialperspective through financial ratios. The results showed that company performance differed for eachperspective.Keywords: Balanced Score Card, financial, customer, business operational, learning and growth perspective